Ammonia-oxidising bacteria not archaea dominate nitrification activity in semi-arid agricultural soil - Banning, Natasha C. (Sci Rep, 2015)
Ammonia-oxidising archaea (AOA) and bacteria (AOB) are responsible for the rate limiting step in nitrification; a key nitrogen (N) loss pathway in agricultural systems. Dominance of AOA relative to AOB in the amoA gene pool has been reported in many ecosystems, although their relative contributions to nitrification activity are less clear. Here we examined the distribution of AOA and AOB with depth in semi-arid agricultural soils in which soil organic matter content or pH had been altered, and related their distribution to gross nitrification rates. Soil depth had a significant effect on gene abundances, irrespective of management history. Contrary to reports of AOA dominance in soils elsewhere, AOA gene copy numbers were four-fold lower than AOB in the surface (0–10 cm). AOA gene abundance increased with depth while AOB decreased, and sub-soil abundances were approximately equal (10–90 cm). The depth profile of total archaea did not mirror that of AOA, indicating the likely presence of archaea without nitrification capacity in the surface. Gross nitrification rates declined significantly with depth and were positively correlated to AOB but negatively correlated to AOA gene abundances. We conclude that AOB are most likely responsible for regulating nitrification in these semi-arid soils.